Characterization of human transition zone reveals a putative progenitor-enriched niche of corneal endothelium - Yam, Gary Hin-Fai (2020)
The corneal endothelium regulates corneal hydration to maintain the transparency of cornea. Lacking regenerative capacity, corneal endothelial cell loss due to aging and diseases can lead to corneal edema and vision loss. There is limited information on the existence of corneal endothelial progenitors. We conducted ultrastructural examinations and expression analyses on the human transition zone (TZ) at the posterior limbus of corneal periphery, to elucidate if the TZ harbored progenitor-like cells, and to reveal their niche characteristics. Within the narrow TZ (~190 μm width), the inner TZ—adjacent to the peripheral endothelium (PE)—contained cells expressing stem/progenitor markers (Sox2, Lgr5, CD34, Pitx2, telomerase). They were located on the inner TZ surface and in its underlying stroma. Lgr5 positive cells projected as multicellular clusters into the PE. Under transmission electron microscopy and serial block face-scanning electron microscopy and three-dimensional (3D) reconstruction, the terminal margin of Descemet’s membrane was inserted beneath the TZ surface, with the distance akin to the inner TZ breadth. Porcine TZ cells were isolated and proliferated into a confluent monolayer and differentiated to cells expressing corneal endothelial markers (ZO1, Na+K+ATPase) on cell surface. In conclusion, we have identified a novel inner TZ containing progenitor-like cells, which could serve the regenerative potential for corneal endothelium.